Inequality in the Greek pension system - Νικολόπουλος, Κωνσταντίνος Β.; Υφαντόπουλος, Γιάννης Ν. (The Greek Review of Social Research, 2010)
In a period of economic crisis the issues related to social insurance and particularly to public pension schemes based on a pay as you go philosophy becomes of a prime importance. The European pension systems present significant financial problems and inadequacies in fulfilling pensioners’ long term expectations. Furthermore due to lack of effective fiscal management, deficits have been observed followed by aggravating problems in the financial and delivery side of pensions. All these contributed to increasing inequalities over the last three decades. The need for efficient social policy intervention is required in order to fulfill the principles of social justice and long term sustainability of the insurance public pension shames The purpose of this study is twofold: First to investigate the inequalities in the financial and delivery side of ten selected pension insurance organizations over the period 1982-2003. Second to examine the evolution of the per capita pension inequalities over the period mid 1980’s to mid 2000’s for selected EU countries. It is witnessed the increasing inequalities in Greece over the above period of time. Policy proposals are discussed to confront the economic and social crisis in the public pension schemes